Ketamine in post-stroke depression: a report of 2 cases - Włodarczyk, Adam; Słupski, Jakub; Szarmach, Joanna; Milewska, Dominika; Cubała, Wiesław J. (Frontiers in Psychiatry, 2025)
BackgroundPost-stroke depression (PSD) is a common comorbidity following a stroke, often leading to significant emotional and physical disability. While antidepressant medications can alleviate depressive symptoms, treatment resistance is frequently observed in PSD patients. Ketamine, an N-methyl-D-aspartate (NMDA) receptor antagonist, has shown potential as a treatment for depression due to its neuroprotective, anti-inflammatory, and psychoplastogenic effects. Its effectiveness in treatment-resistant post-stroke depression (TRD-PSD) remains underexplored.MethodsTwo patients diagnosed with treatment-resistant post-stroke depression were treated with intravenous ketamine. Ketamine infusions were administered over a 4-week period in both cases, and the patients’ depressive symptoms were closely monitored.ResultsBoth patients demonstrated improvement in depressive symptoms following ketamine treatment. The treatment was well tolerated, with minimal side effects reported, and no significant adverse events were observed during the treatment course.ConclusionsKetamine may be a viable treatment option for patients with treatment-resistant post-stroke depression. Further research is warranted to better understand the efficacy and safety of ketamine in this specific patient population.